Analisis Kendala Siswa Kelas II Sekolah Dasar dengan Kemampuan Pemecahan Masalah Matematis pada Materi Operasi Hitung Perkalian - Susanti, Fida Anggraeni; Supriadi, Supriadi (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The ability to solve mathematical problems is mandatory for students to learn, because it is very useful for everyday life. The purpose of this study was to determine the obstacles of second grade students of SDN Cibeber I to experience difficulties in solving mathematical problem solving of multiplication material. This research approach uses qualitative and is carried out with a case study method. The subjects of this study were 4 second grade students of SDN Cibeber I. After being analyzed, it was found that students experienced problems solving mathematical problem solving with multiplication material. They are difficulty to understand the questions given correctly, to plan strategies in order to solve problems, to calculate solving problems properly and correctly, and to make conclusions from the results obtained. The solution to solving students' problems in solving mathematical problem-solving problems in multiplication arithmetic operations is that students often practice problems solving problems such as story problems, memorizing multiplication, and not rushing to work on problems because to solve them. Problem solving skills involve ability to remember, understand, apply, analyze, and evaluate. When students can understand the problem or are able to identify what is known and asked from the questions given, the students can identify several strategies or plans that can be used to solve the problem. Thus, students who are able to identify several strategies or plans that can be used to solve these problems, the students can use the appropriate formula. Then, students can use the appropriate formula, then students can calculate problem solving and draw conclusions from the results obtained.